Sugar-Sweetened Beverages, Adolescent Obesity, and Preventive Strategies: A Systematic Review - Luthfia Ranie Amaliasari; Laila Hasanati Sholehah; Aliya Hegar Nugrahani (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2026)
Abstract The consumption of sugar-sweetened beverages (SSBs) has risen significantly over the past three decades and has become a major risk factor for adolescent obesity. This article aims to review global and national trends in SSB consumption and their implications for adolescent obesity prevalence. The method applied was a literature review of epidemiological studies, meta-analyses, global health survey reports, and national data. Findings indicate that more than 30% of adolescents worldwide consume SSBs daily, with the highest prevalence in Latin America and the Caribbean. In Indonesia, the 2023 National Health Survey reported that nearly half of adolescents consume sugary drinks every day. Excessive SSB intake contributes to increased caloric intake, insulin resistance, hormonal imbalance, and altered eating behaviors leading to higher body mass index. Both mechanistic and epidemiological evidence consistently demonstrate a significant association between SSB consumption and adolescent obesity, with greater risks observed among those with higher daily intake. Environmental factors, modern dietary patterns, sedentary lifestyles, and psychosocial stressors further exacerbate the condition. In conclusion, SSB consumption is a critical determinant of adolescent obesity, and prevention strategies require a comprehensive approach involving nutrition education, school environment regulation, parental engagement, and public health policies. Keywords: sugar-sweetened beverages, adolescent obesity, epidemiology, lifestyle, public health